PERSEPSI KONSUMEN TERHADAP KUALITAS PELAYANAN DALAM PROSES PEMBELIAN BERAS HITAM ORGANIK PRODUKSI GAPOKTAN WANGUNSARI CISAYONG TASIKMALAYA - Wima Hatami; Kuswarini Kusno; Agriani Hermita Sadeli; Sulistyodewi Nur Wiyono (Universitas Galuh, 2022)
Public awareness of the importance of healthy living and increasing environmental sustainability has also encouraged some people to consume organic food, one of which is organic black rice. Gapoktan Wangunsari is one of the producers of organic black rice. The price of organic black rice produced by Gapoktan Wangunsari is relatively cheap. The organic black rice has four organic certifications, pesticide-free food and chemical fertilizer certification. It should be able to attract consumers' interest, but in fact, only a few consumers are interested in. Perceptions of good service quality will have an impact on loyalty and repeat purchases by consumers. In addition, the quality of service is difficult to imitate by other manufacturers. The purpose of this study was to determine the characteristics of consumers and to analyze consumer perceptions of service quality in the process of purchasing organic black rice produced by Gapoktan Wangunsari. The research design uses a quantitative design with survey techniques. The results showed that the majority of consumers live in rural areas, are female, aged 56 years, have secondary education, work as farmers and belong to the lower middle income class, namely < IDR 2,600,000 per month. Consumer perceptions of service quality in the process of purchasing organic black rice are very good. Wangunsari Gapoktan should do promotions and sales online so that the number of consumers increases.